2017
DOI: 10.1080/10942912.2017.1359186
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic composition as measured by liquid chromatography/mass spectrometry and biological properties of Tunisian barley

Abstract: In this work, phenolic composition, antioxidant and antibacterial activities of selected Tunisian barley varieties were studied. Swihli barley exhibited the highest total phenolic content and the strongest antioxidant and antibacterial activities. Liquid chromatography/mass spectrometry analysis revealed significant qualitative and quantitative differences in phenolic composition among the different varieties. Procyanidin B3 and catechin were the most abundant. Pearson's correlation test revealed significant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…It was observed that 80% methanol and 50% acetone yielded better extraction efficiency and phenolic identification; a similar behavior was observed in the quantification of total phenols. [45,46] have reported that flavonols are the most abundant phenolic fraction, which concurs with data reported for barley husk. Studies of phenolic compounds in barley husk are limited.…”
Section: Identification and Quantification Of Phenolic Compoundssupporting
confidence: 86%
“…It was observed that 80% methanol and 50% acetone yielded better extraction efficiency and phenolic identification; a similar behavior was observed in the quantification of total phenols. [45,46] have reported that flavonols are the most abundant phenolic fraction, which concurs with data reported for barley husk. Studies of phenolic compounds in barley husk are limited.…”
Section: Identification and Quantification Of Phenolic Compoundssupporting
confidence: 86%
“…The results were lower than those of Zeitoun et al (2017) and Thalhaoui et al (2016) who fined in dried leaves IC50 values of 427.00 ± 23.5 µg.mL -1 and 129.9 ± 23.5 µg.mL -1 respectively. Furthermore, the hereby obtained results were in accordance with those of Boubakri et al (2017), who explained that the IC50 were 44.83 ± 0.35 µg.mL -1 and 58.08 ± 3.5 µg.mL -1 of Swihli and Rihane extracts respectively.…”
Section: Radical-scavenging Activities On Dpphsupporting
confidence: 92%
“…In addition, the contents (216.68 mg/100 g DW) of the bound and total phenolics of the blue highland barley planted in Qinghai are higher than those planted in Lhasa (Tibet) and Hezuo (Gansu), which is related to the fact that the content of phenolic can be improved by promoting the synthesis of plant phenylalanine ammonia lyase at low temperature [ 29 ]. Moreover, the average content of blue highland barley varieties in the three locations is higher than those of Croatia [ 30 ] (148.01–159.00 mg GAE/100 g DW) and Tunisian barley [ 31 ] (40.01–123.00 mg GAE/100 DW). In addition, the contents of free, bound and total flavonoids of the blue highland barley planted in Menyuan (Qinghai) and Lhasa (Tibet) show no significant difference, among which the content of free flavones of the blue highland barley planted in Lhasa (Tibet) (255.2 mg/100 g DW) is the highest.…”
Section: Resultsmentioning
confidence: 99%